BRIDGING THE GAPS : A PARADIGMATIC INSIGHT INTO PHILOSOPHY OF LAW - Erlyn Indarti (Fakultas Hukum, Universitas Diponegoro, 2016)
Paradigm represents a worldview that defines, for its holder, the nature of theworld, the individual's place in it, and the range of possible relationships to thatworld and its parts. It comprises of four main elements, i.e. ontology, epistemology,methodology, and methods. Within the discipline of law, there seem to be two setsof gaps separating philosophy of law's building blocks that dissociate, first, legalpractice from legal theory and, second, legal science from legal philosophy. It isthe purpose of this article, with the help of paradigmatic insight, to bridge thosegaps.Keywords: law, philosophy of law, paradigm, paradigmatic study of law